Daily field checking list by Walter Rosene, April 23, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, Robert Walker and Buddy Sturtz, April 23, 1939. Also notes they banded all three young Great Horned Owls and in the process of banding Robert Walker was struck once by one of the old Great Horned Owls. Plustek--flatbed